Practising colonial medicine : the Colonial Medical Service in British East Africa - Crozier, Anna (I.B. Tauris : Distributed by St. Martins Press in the U.S., 2007)
The role of the Colonial Medical Service - the organisation responsible for healthcare in British overseas territories - goes to the heart of the British Colonial project. "Practising Colonial Medicine" is a unique study based on original sources and research into the work of doctors who served in East Africa. It shows the formulation of a distinct colonial identity based on factors of race, class, background, training and Colonial Service traditions, buttressed by professional skills and practice. Anna Crozier analyses all aspects of recruitment, qualifications, training as well as